2010
DOI: 10.2460/ajvr.71.7.726
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the use of antimicrobials and the effects on productivity of swine farms in Denmark

Abstract: From 1992 to 2008, antimicrobial consumption per kilogram of pig produced in Denmark decreased by > 50%. Furthermore, there was improvement in productivity, suggesting that long-term swine productivity was not negatively impacted by a ban on AGP use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 13 publications
1
95
0
2
Order By: Relevance
“…B 370: 20140085 under modern circumstances with improved feeding regimes to compare with the situation 40-60 years ago. It has been argued that this use is essential to feed the world with animal proteins but more recent data suggest that the importance of antimicrobial growth promoters (AGPs) might be over-estimated [18][19][20][21].…”
Section: Antimicrobial Usage In Livestock Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…B 370: 20140085 under modern circumstances with improved feeding regimes to compare with the situation 40-60 years ago. It has been argued that this use is essential to feed the world with animal proteins but more recent data suggest that the importance of antimicrobial growth promoters (AGPs) might be over-estimated [18][19][20][21].…”
Section: Antimicrobial Usage In Livestock Productionmentioning
confidence: 99%
“…Initial analysis only looking at production parameters the year before and the year after the ban of AGPs suggested that this was without any effect in older pigs, but associated with increased mortality and reduced average daily gain in weaners. In 2010, a study was published analysing the trends of a number of available production parameters from 1992 to 2008 [18]. Figure 3 gives an update of these data including an additional 5 years of data from 2009 to 2013, as well as an additional inclusion of piglet mortality in the period [2003][2004][2005][2006][2007][2008][2009][2010][2011][2012][2013].…”
Section: Effect Of Interventions On Livestock Health Welfare and Promentioning
confidence: 99%
“…However, currently available studies find mixed evidence for the impact of NEMP on antibiotic prescription in primary care: despite some potential improvements, overuse and irrational use of antibiotics remains a prevalent problem. [82][83][84][85] Responsible use in the animal sector AMR in animals represents a significant problem for human health [86][87][88] and the emergence of multidrug resistant bacterial strains and strains resistant to antimicrobials considered critically important in human medicine is of concern. [89][90][91] Bacteria hosted by animals can reach humans through direct contact, food and/or the environment.…”
Section: Case Study 2: Antibiotic Prescription In China: Systemic Andmentioning
confidence: 99%
“…13 These results can serve notice to agricultural companies that there is indeed an added financial benefit to discontinuing use of prophylactic antibiotics in livestock. Nonetheless, our fundamental shortcoming is the Canadian government's reluctance to act upon such evidence.…”
Section: Although Danish Antibioticmentioning
confidence: 99%